2022
DOI: 10.4049/jimmunol.2100830
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Immune Profiling Reveals CD56+ Monocytes and CD31+ Endothelial Cells Are Increased in Severe COVID-19 Disease

Abstract: Immune response dysregulation plays a key role in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pathogenesis. In this study, we evaluated immune and endothelial blood cell profiles of patients with coronavirus disease 2019 (COVID-19) to determine critical differences between those with mild, moderate, or severe COVID-19 using spectral flow cytometry. We examined a suite of immune phenotypes, including monocytes, T cells, NK cells, B cells, endothelial cells, and neutrophils, alongside surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…These cells are associated with IFN-γ and granzyme B secretion and highactivated pro le; their number increase in the rst ve days of infection and they remain proliferative at the sixteenth day after the PCR test con rmation. CD56 + monocytes probably participate in the exacerbated immune response that lead to tissue and organ damage and dysfunction in COVID-19 and the frequency of these cells positively correlate with hypertension in these patients [45].…”
Section: Discussionmentioning
confidence: 97%
“…These cells are associated with IFN-γ and granzyme B secretion and highactivated pro le; their number increase in the rst ve days of infection and they remain proliferative at the sixteenth day after the PCR test con rmation. CD56 + monocytes probably participate in the exacerbated immune response that lead to tissue and organ damage and dysfunction in COVID-19 and the frequency of these cells positively correlate with hypertension in these patients [45].…”
Section: Discussionmentioning
confidence: 97%
“…For example, in patients with COVID-19, the number of CD14++CD16− T lymphocytes is typically low, while CD14++CD16+ (intermediate) and CD14+CD16++ (non-classical) monocytes increase [ 38 , 39 ]. Recently described CD56+CD14+Ki67+IFN-γ+ monocyte may play a crucial role in severe COVID-19 [ 40 ].…”
Section: Immunology Of Mis-cmentioning
confidence: 99%
“…In children, novel insights showed that the typical polyclonal Vβ21.3+ T cell expansions might be associated with MIS-C [ 40 ]. The activated phenotype of Vβ21.3+ T cells express high levels of CX3CR1, a marker of patrolling monocytes and cytotoxic lymphocytes.…”
Section: Immunology Of Mis-cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because many of the necrotic myocytes showed evidence of contraction band necrosis, we believe that the majority injury is due to microvascular/endothelial injury and consequent ischemia/reperfusion injury. Interestingly, a recent report by Dutt et al demonstrates that enhanced circulating endothelial cells (CD452CD31+ CD34+ CD146+), circulating endothelial progenitors (CD452CD31+ CD34+/2CD1462), and neutrophils (CD11b+ CD66b+) correlated with the severity of COVID-19 disease suggesting that SARS-CoV-2 infection causes damage and increased turnover of endothelial cells [9] . In our recent review article we pointed out a possible important role of monocyte-derived macrophages in the pathogenesis of severe COVID-19 induced myocardial damage either by causing a cytokine-mediated endothelial damage and/or by causing localized endothelial damage/apoptosis [10] .…”
mentioning
confidence: 98%